Pediatric multiple sclerosis: analysis of clinical and epidemiological aspects according to National MS Society Consensus 2007 Esclerose múltipla pediátrica: análise de aspectos clínicos e epidemiológicos de acordo com o Consenso de 2007 da Sociedade Americana de Esclerose Múltipla - Maria Lúcia Brito Ferreira; Maria Íris Morais Machado; Maria José Guedes Dantas; Álvaro José Porto Moreira; Adélia Maria de Miranda Henriques Souza (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To describe the epidemiological and clinical characteristics of child/adolescence multiple sclerosis (MS). METHOD: According to a descriptive, cohort study, with comparison of groups, data of 31 cases of child/adolescent MS, diagnosed at State Reference Center for Demyelinating Diseases - Hospital da Restauração, Recife, Pernambuco, Brazil, from 1987 to July 2007, were analyzed. The variables were: sex, initial symptoms, time for diagnosis, time of disease onset (early childhood, later childhood and adolescence), time of follow-up, number of relapses, relapses index and disability. Using SPSS software, version 13.0, t Student and Mann-Whitney tests were performed, with significance level of 0.05. RESULTS: There were 3 (9.7%) cases of early childhood MS, 9 (29%), of late childhood MS, and 19 (61.3%), of adolescence MS. The general sex rate female: male was 1.8:1, varying according to age of onset. The predominant deficits were motor (12; 38.7%) and brainstem/cerebellum (7; 22.5%) especially on subsequent relapses of relapsing/remitting form. Time for diagnosis and average relapses index were higher in early childhood than in adolescence class (p=0.049 and p=0.028, respectively). Disability was higher for primary and secondary MS, as well as for early childhood. CONCLUSION: Early childhood MS presents proper and different characteristics from adults, consisting in a difficult diagnosis that demands aid of expert neurologist on MS. OBJETIVO: Descrever características epidemiológicas e clínicas de casos de esclerose múltipla (EM) de início precoce. MÉTODO: Em estudo descritivo, prospectivo, tipo coorte, com comparação de grupos, foram analisados 31 portadores de EM de início precoce, diagnosticados no Centro Estadual de Referência para Atenção a Pacientes Portadores de Doenças Desmielinizantes do Hospital da Restauração, Recife, Pernambuco, entre 1987 e julho de 2007. As classes ao primeiro surto foram: infantil precoce, infantil tardia e juvenil, e as variáveis: sexo; sintomas iniciais; tempo para diagnóstico, de doença e de seguimento; número de surtos, índice de recidivas e EDSS. Com o programa SPSS, versão 13.0, foram utilizados os testes t de Student e Mann-Whitney com nível de significância de 0,05. RESULTADOS: Foram observados 3 (9,7%) casos de EM infantil precoce, 9 (29%), infantil tardia, e 19 (61,3%), juvenil. A razão geral de sexo feminino:masculino igualou-se a 1,8:1, variando segundo idade de início. Predominou comprometimento motor (12; 38,7%) e de tronco encefálico ou cerebelo (7; 22,5%), especialmente nos surtos subseqüentes da forma surto-remissão. O tempo para diagnóstico e o índice médio de recidivas foram maiores na infantil precoce que na juvenil (p=0,049 e p=0,028, respectivamente. O grau de incapacidade foi maior nas formas primária e secundária progressiva, assim como na infantil precoce. CONCLUSÃO: A EM na infância e adolescência apresenta características próprias, diferentes daquelas do adulto, constituindo-se em diagnóstico difícil, que exige auxílio de especialista em EM.